PENGARUH MOTIVASI BELAJAR DAN GAYA BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS IX SMP YP PGRI 4 MAKASSAR - Alfonsius Nceong; Elisabet Reting (Pojok Publisher, 2024)
The Influence of Learning Motivation and Learning Style on the Achievement of Social Studies of Grade IX Students of SMP YP PGRI 4 Makassar. The purpose of this study was to determine the influence of learning motivation and learning style on the achievement of social studies of grade IX students of SMP YP PGRI 4 Makassar. The type of quantitative research. Data collection in the form of questionnaires and questionnaires and documentation. the number of population in this study was 39 and the samples taken were 39. Data analysis used multiple linear regression analysis tools. The results of this study indicate that learning motivation has a significant positive effect on learning achievement, because it obtains a Tcount value of 3.140> Ttable 1.688 and a significance value of 0.003 <0.05; Learning style does not have a significant positive effect on learning achievement, because it obtains a tcount value of -1.980 <ttable 1.688 and a significance value of 0.55> 0.05; Learning motivation and learning style simultaneously have a significant positive effect on learning achievement, because the F count value is 5.815, which is greater than the F table of 3.259 and the sig value is 0.006 <0.05 for IPS students in class IX of SMP YP PGRI 4 Makassar.